2004
DOI: 10.1016/j.ejcts.2003.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Using jugular bulb oxyhemoglobin saturation to guide onset of deep hypothermic circulatory arrest does not affect post-operative neuropsychological function

Abstract: Monitoring of SjO(2) had no apparent effect upon post-operative neuropsychological outcome, and there were no trends in our small patient cohort suggesting differences that our study was not adequately powered to detect. Use of SjO(2) monitoring was associated with more profound hypothermia prior to DHCA due to more prolonged cooling in attempts to bring the SjO(2) above the 95% threshold. Using our institutional cooling protocol, SjO(2) monitoring does not appear to increase neuroprotection in patients underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
2
3
0
1
Order By: Relevance
“…However, in another study in 2007, being consistent with the results of the present one, they reported no significant differences between normothermic and hypothermic methods at the time of discharge, with the difference that the hypothermic method was employed without rewarming in the present study (19). Consistent with the results of the present study, other studies showed no significant differences in cognitive functions between the two normothermic and hypothermic methods at the time of discharge (19)(20)(21)(22). Hiraoka et al used the MMSE questionnaire to survey cognitive functions of patients after aortic arch replacement surgery.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, in another study in 2007, being consistent with the results of the present one, they reported no significant differences between normothermic and hypothermic methods at the time of discharge, with the difference that the hypothermic method was employed without rewarming in the present study (19). Consistent with the results of the present study, other studies showed no significant differences in cognitive functions between the two normothermic and hypothermic methods at the time of discharge (19)(20)(21)(22). Hiraoka et al used the MMSE questionnaire to survey cognitive functions of patients after aortic arch replacement surgery.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, based on cognitive function assessments for the periods of two weeks and six months after surgery, cognitive impairment would gradually improve over time in both groups, indicating that more noticeable cognitive impairment occurred during hospitalization (15). The reason is that most studies have shown that severity of cognitive impairment decreases over time compared to the first days of hospitalization (15,21,22). The present study also showed a decrease in cognitive impairment in the last two days, i.e.…”
Section: Discussionsupporting
confidence: 56%
“…76 It also showed that NIRS oximetry has largely replaced invasive jugular bulb oximetry. 76,86 An analysis of open arch surgical strategies at 12 large European centres reported NIRS use for neuromonitoring in all centres. 87 The limitation remains that uneventful intraoperative bifrontal regional cerebral oximetry saturation (rSO 2 ) tracings do not rule out focal cerebral ischaemia, which may occur outside the limited field of view of current NIRS devices.…”
Section: Near-infrared Spectroscopy-based Regional Oxygenation Monitomentioning
confidence: 99%
“…Einige Autoren emp fehlen, die Patienten vor einem DHCA so lange zu kühlen, bis die S vj O 2 Werte um 95% erreicht, um eine maximale zerebrale metabolische Suppression zu gewährleis ten [3,13]. Allerdings wurde bezweifelt, dass während eines DHCA eine Orien tierung an der S vj O 2 zur Beurteilung einer adäquaten Hypothermie auch zu einer verbesserten Neuroprotektion führt [44]. Aufgrund der Invasivität des Verfahrens sehen einige Autoren in der Messung der S vj O 2 nur eine begrenzte Einsatzmöglich keit im klinischen Alltag [14].…”
Section: Zerebrales Neuromonitoringunclassified